Investigation of Sunk Cost Fallacy in European Football - Empirical Evidence from English Premier League and German Bundesliga - Selçuk Özaydın (Pamukkale University, 2022)
Sunk cost fallacy is a behavioral decision-making concept that leads to biased decisions and sub-optimal outcomes. Although academics have shown some interest in this phenomenon, only a few studies investigate the presence of sunk cost fallacy in European football. This study investigates whether the sunk cost fallacy exists in Europe's top two football leagues using transfer fees and playing time. The presence of sunk cost fallacy would indicate a faulty decision-making process. The conducted regression continuity design results suggest that the coaches in the English Premier League make biased decisions due to sunk cost fallacy, whereas the coaches in German Bundesliga do not. The biased decisions of Premier League managers indicate managerial inefficiency, which might lead to undesired outcomes.